Qualidade de vida de pacientes com queimaduras internados em um hospital de referência no nordeste brasileiro - Guimarães, Isaac Bevilaqua de Albuquerque (2013)
Objective: Despite scientific advances, the burns are still a medical, psychological, social and economic problem that involves not only the doctor and the patient as well as the whole society. Individuals who have suffered extensive burns have physical and psychological changes; the impact on their quality of life (QOL) constitutes a major challenge to professionals responsible for their treatment. This study aims to evaluate the QOL of burned patients while hospitalized in an institution of reference. Methods: Twenty burned patients were evaluated by the application of the questionnaire “The Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36)”, adapted and validated for the Portuguese language. Results: Low educational level and the prevalence of male patients were identified. The most frequent causal agent was alcohol. SF-36 best results were found in the areas vitality (77) and mental health (57.6) while the worst results were identified in the fields “physical aspects” (0) and emotional aspects (0). Conclusions: According to the answers received, the positive meaning of quality of life relates primarily to the areas “Vitality” and “Mental State”. The areas with greater commitment are “Physical and Emotional aspects”, reflecting the perception of their self-image taking into account the burns they suffered.